Quantitative robustness of regularity for 3D Navier–Stokes system in Ḣα-spaces. (October 2016) - Burczak, Jan; Zaja̧czkowski, Wojciech M.
Abstract: We present stability and regularity results for the 3D incompressible Navier–Stokes system in a periodic box, in H ̇ α spaces, with α ∈ [ 1 / 2, 1 ] . A special attention is paid to obtaining quantitative results, i.e. ones with explicit or at least computable constants, and to scaling.